Cultural Synergy and Sustainability in Improving Tax Compliance of West Sulawesi MSMEs - Abdul Galib; Nurwahyuni Syahrir; Hasnidar Hasnidar (Jurnal Proaksi, 2025)
Main Purpose -  This study aims to reveal the role of awareness of sustainable practices, culture, and perceived behavioral control in improving tax compliance as an effort to maintain sustainable business practices for MSMEs in West Sulawesi by internalizing the Pappasang Kalindaqdaq Mandar.Method -  The research method used in this study is a mixed method with a concurrent model to analyze quantitatively and qualitatively simultaneously.Main Findings -  The results confirmed the theory of planned behavior, whereby awareness of sustainable practices and culture has a significant influence on increasing MSMEs' intention to behave in a compliant manner towards taxation, but perceived behavioral control did not have a significant influence. These findings indicate that aspects of awareness of sustainable practices and internalization of Pappasang Kalindaqdaq Mandar culture have a strong dominance in explaining MSME tax compliance in West Sulawesi.Theory and Practical Implications - The strong dominance of tax awareness and culture, but not accompanied by a significant influence on perceived behavioral control, requires further investigation. Further in-depth interviews are needed to obtain more in-depth information from tax authorities and MSMEs to uncover the actual role of control. Novelty -  This research explores non-economic aspects from various perspectives such as awareness of sustainable practices (internal), culture (external), and perceived behavioral control (control belief) in improving tax compliance (external).